2015
DOI: 10.1152/ajpendo.00550.2014
|View full text |Cite
|
Sign up to set email alerts
|

Hypoenergetic diet-induced reductions in myofibrillar protein synthesis are restored with resistance training and balanced daily protein ingestion in older men

Abstract: -Strategies to enhance weight loss with a high fat-to-lean ratio in overweight/obese older adults are important since lean loss could exacerbate sarcopenia. We examined how dietary protein distribution affected muscle protein synthesis during energy balance (EB), energy restriction (ER), and energy restriction plus resistance training (ER ϩ RT). A 4-wk ER diet was provided to overweight/obese older men (66 Ϯ 4 yr, 31 Ϯ 5 kg/m 2 ) who were randomized to either a balanced (BAL: 25% daily protein/meal ϫ 4) or ske… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
106
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 98 publications
(114 citation statements)
references
References 53 publications
(69 reference statements)
4
106
0
Order By: Relevance
“…A recent study by Murphy and colleagues (2015) found that MPS responses (specifically the myofibrillar fraction) of older, overweight men to acute protein feeding in energy deficit (4 weeks of energy restriction, ∼300 kcal day −1 ) could be partly rescued by consuming a balanced daily distribution of protein (25% per meal) during energy deficit as opposed to consuming the majority of protein in an evening meal. A complete restoration of MPS was mitigated by REX training in weeks 3 and 4 of the energy deficit period, but these MPS values still failed to exceed that of resting energy balance ( presumably from intrinsic factors of anabolic resistance in this population) (Murphy et al, 2015). These data support the notion that prior REX sensitizes the protein synthetic machinery to amino acid ingestion Moore et al, 2009b).…”
Section: Reduced Energy Availabilitysupporting
confidence: 64%
See 1 more Smart Citation
“…A recent study by Murphy and colleagues (2015) found that MPS responses (specifically the myofibrillar fraction) of older, overweight men to acute protein feeding in energy deficit (4 weeks of energy restriction, ∼300 kcal day −1 ) could be partly rescued by consuming a balanced daily distribution of protein (25% per meal) during energy deficit as opposed to consuming the majority of protein in an evening meal. A complete restoration of MPS was mitigated by REX training in weeks 3 and 4 of the energy deficit period, but these MPS values still failed to exceed that of resting energy balance ( presumably from intrinsic factors of anabolic resistance in this population) (Murphy et al, 2015). These data support the notion that prior REX sensitizes the protein synthetic machinery to amino acid ingestion Moore et al, 2009b).…”
Section: Reduced Energy Availabilitysupporting
confidence: 64%
“…As MPS is energetically expensive, it is hardly surprising that periods of energy deficit attenuate resting-, fasted- (Areta et al, 2014;Murphy et al, 2015;Pasiakos et al, 2010) and feedinginduced MPS (Murphy et al, 2015;Pasiakos et al, 2013). However, the magnitude to which energy deficit affects post-REX MPS responses has received little attention.…”
Section: Reduced Energy Availabilitymentioning
confidence: 99%
“…Although alterations of skin structure are visible features of aging, there is only incomplete knowledge about the relation between normal or altered diet and skin aging, in particular when compared with the huge amount of published literature dealing with aging, diet, and peripheral muscle maintenance [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…One month later, myofibrillar protein synthesis was stimulated more by the diet with evenly than with unevenly distributed dietary protein in both the presence and absence of resistance training. 78 Although neither study determined precise muscle weight and force, both showed that skewed dietary protein intake with the highest consumption of dietary protein in the evening stimulated less muscle-protein synthesis than a balanced distribution of daily protein intake. Whether or not the molecular clock in skeletal muscle is relevant to the different rates of muscle protein synthesis caused by the distribution of dietary protein intake remains unknown.…”
Section: Chrononutritionmentioning
confidence: 95%
“…77 Murphy et al implemented a randomized trial that included overweight and obese older men (age, 66±4 years; BMI, 31±5). 78 One group was given a diet with evenly distributed protein across all daily meals (~25% of total protein intake at breakfast, lunch, dinner, and pre-bedtime snack). The other group received most of the dietary protein at dinnertime (about 7% of total protein intake at breakfast, 17% at lunch, 72% at dinner, and 4% as a pre-bedtime snack).…”
Section: Chrononutritionmentioning
confidence: 99%